ORGANIZATIONAL EVALUATION WITH THE ORGANIZATIONAL EFFECTIVENESS CHECKLIST (OEC) APPROACH - Mahjudin Mahjudin (Journal of Managerial Sciences and Studies, 2023)
Along with the growth rate of laying hen farms in Indonesia, SME’’S X, which is a laying hen breeder, has been doing business in this field for a long time and wants to expand. The expansion is carried out to add new customers, because the growth in the number of customers is less significant than the amount of production. In addition, SME’’S X often gets error reports from both production and sales. To expand, SME’’S X needs to improve the company's internal conditions first. Currently SME’’S X is carrying out repairs, but the improvements or developments that have been made have little impact, because the owner does not have clear priorities and standards to use. This study aims to evaluate the organizational effectiveness of SME’’S X. See how far SME’’S X has been effective or not in managing the organization and provide recommendations for improvements to the indicators in each criterion that need to be improved. To evaluate the effectiveness of a company using the Organizational Effectiveness Checklist (OEC), there are stages in determining indicators, identifying priorities and determining performance standards. Identification of the assessment of each indicator is carried out by means of interviews with experts and weighting is carried out which is processed using AHP to determine the priority of selected indicators that must be considered first. The results of the overall evaluation calculation, the effectiveness value of SME’’S X is 3.546. That SME’’S X is in a safe condition but needs to improve three criteria, namely growth, stability, and information management in increasing the effectiveness of the company